3b-2g+4b+7b=

Simple and best practice solution for 3b-2g+4b+7b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3b-2g+4b+7b= equation:


Simplifying
3b + -2g + 4b + 7b = 0

Reorder the terms:
3b + 4b + 7b + -2g = 0

Combine like terms: 3b + 4b = 7b
7b + 7b + -2g = 0

Combine like terms: 7b + 7b = 14b
14b + -2g = 0

Solving
14b + -2g = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '2g' to each side of the equation.
14b + -2g + 2g = 0 + 2g

Combine like terms: -2g + 2g = 0
14b + 0 = 0 + 2g
14b = 0 + 2g
Remove the zero:
14b = 2g

Divide each side by '14'.
b = 0.1428571429g

Simplifying
b = 0.1428571429g

See similar equations:

| 9k^3x+36k^2x^2+36kx^3=0 | | 2x+12=-2x-8 | | .8(1+.5x)=.1(12+x) | | (7c+5)(3c-6)=0 | | 2(4x+2)=6x+2x+4 | | 6x+26=10x+18 | | -9(b^2+2b-3)+b(2b+5)+7= | | x^2-129x=0 | | 190+0.15x=322 | | -6(g+4)=12 | | -(8y+2)-(-7y-8)=-1 | | 4x+16=26 | | Y=(6x+3)(5x+4) | | x+11=11-5x | | 7w-4w-8=7 | | h+(-3)+9=-1+14 | | -6x^2+5x-2=0 | | 10a=3a+9+6a | | Y-16=11(x-1) | | b^4-5b^2-6b=0 | | .77=(1/x) | | x^4+9x^2+4=0 | | .77=1/x | | x/24-1.4=8.3 | | (X+4)-x-(5-6x)=11 | | Y=(6x+3)10 | | 8x+6y=-26 | | 2a+4(2-a)-6(1+a)=18 | | m+(-6)=22 | | 15+4ln(x)=10 | | Z-19=19 | | 2(x+6)=-2x(x-4) |

Equations solver categories